Comparative statics of altruism amd spite - Igal Milchtaich (Bar-Ilan University, Department of Economics, 2008)
The equilibrium outcome of a strategic interaction between two or more people may depend on the weight they place on each other's payoff. A positive, negative or zero weight represents altruism, spite or complete selfishness, respectively. Paradoxically, the real, material payoff in equilibrium for a group of altruists may be lower than for selfish or spiteful groups. However, this can only be so if the equilibria involved are unstable. If they are stable, the total (equivalently, average) payoff can only increase or remain unchanged with an increasing degree of altruism.
Keywords: C62; C72; D64; 330; altruism; spite; comparative statics; strategic games; stability of equilibrium; Altruismus; Gleichgewichtsstabilität; Spieltheorie; Nichtkooperatives Spiel